Between self and author : an autoethnographic approach towards the crafting of reflexive compositions in post graduate drama studies - Moyo, Awelani Lena (Rhodes University, Faculty of Humanities, Department of Drama, 2009)
This thesis explores the merits of reflexivity in the processes of creating a performance and of performing research in Drama Studies. In it, I make a case for the validity of autobiographical material as an aid to generating such reflexivity. Through an autoethnographic case study of my work entitled Compositions (a series of performance projects) in which I focus on the theme of migration, I provide an indepth account of my experiences, focusing specifically on the interrelated concerns of body, space and journey in my ritualistic performance. My examination explores the dynamic effects of liminality within identity politics, through which I foreground several issues of concern which I have encountered as an emerging scholar and theatremaker working within an academic institution. I propose that the process of studying drama in a University ultimately requires one to continually negotiate a range of subject positions, whilst finding connections between these various identities that one may take up during the course of one's studies. By developing an awareness of the overlapping of such identities and inhabiting the spaces in-between subject positions, I demonstrate how taking into account one's personal lived experience can help illuminate one's understanding of both the work of art and the research report, as well as the broader contexts in which such practice-based work exists. I illustrate how such an understanding has ultimately maximised the knowledge and learning that I have gathered, and has contributed to the crucial project of developing my authorial voice in writing and performance, which is central to the aims of the Master of Arts degree in Drama.
Keywords: Drama -- Study and teachng (Higher); College and school drama